Nutritional-inflammatory status and diabetic retinopathy: exploring the association between advanced lung cancer inflammation index and retinal complications in diabetes - Peng, Jinxiang; Chen, Zhuang; Wang, Yanqiong; Wang, Kui; Wu, Feng; Xiang, Jianjun (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to assess the association between the advanced lung cancer inflammation index (ALI) and the prevalence of diabetic retinopathy (DR) in a nationally representative sample of US adults with diabetes.MethodsWe used cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) spanning 1999 to 2018. ALI was calculated from the body mass index (BMI), albumin levels, and neutrophil-to-lymphocyte ratio (NLR), providing an integrative measure of inflammatory and nutritional metabolic status. A history of diabetes was obtained through self-report. Logistic regression models were used to investigate the relationship between ALI and DR prevalence, adjusting for multiple potential confounders. Additionally, restricted cubic spline (RCS) analyses were used to explore potential non-linear associations.ResultsA total of 3,952 diabetic participants were included, of whom 813 had DR. Logistic regression analysis shows that higher ALI values are significantly correlated with a decrease in DR prevalence. Compared to the lowest ALI quartile, the highest quartile was associated with a 27% decrease in DR prevalence after full adjustment. Subgroup analyses showed that the relationship remained stable across most demographic and clinical strata, although racial differences were also observed. Furthermore, RCS analyses revealed an L-shaped relationship between ALI and DR prevalence.ConclusionIn the US adult diabetic population, lower ALI levels were associated with greater DR prevalence, and this relationship displayed an L-shaped, non-linear pattern. These findings suggest that monitoring and managing ALI may be beneficial in reducing the risk of DR. Future longitudinal studies are needed to clarify the causality and evaluate the impact of ALI-targeted interventions in clinical practice.